The Effect of Authoritarian Leadership Style and Employee Training on Employee Training on Employee Performance Mediated by Work Motivation at PT.Ume Persada Indonesia - Hilmi, Hadiyan Z; Soelistya, Djoko (LP2M IAIN Palopo, 2024)
This research was conducted to find out what affects employee performance at PT Ume Persada Indonesia. This study aims to analyze the effect of Authoritarian Leadership Style on Employee Performance, Employee Training on Employee Performance, Authoritarian Leadership Style on Work Motivation, Employee Training on Work Motivation, Work Motivation on Employee Performance, Authoritarian Leadership Style on Employee Performance through Work Motivation as Mediation, and Employee Training on Employee Performance through Work Motivation as Mediation. The research method used in this research is quantitative research. The population in this study were all employees of PT Ume Persada Indonesia and a saturated sample of 149 respondents. Data analysis using Smart-PLS 4.0. The results showed that Authoritarian Leadership Style (X1) and Employee Training (X2) had a positive and significant influence on Employee Performance (Y). Authoritarian Leadership Style (X1) and Employee Training (X2) have a positive and significant influence on Work Motivation (Z). Work Motivation (Z) has a positive and significant influence on Employee Performance (Y). Authoritarian Leadership Style (X1) and Employee Training (X2) have a significant influence on Employee Performance (Y) through Work Motivation (Z) as mediation. From the research results PT Ume Persada Indonesia needs to combine leadership styles, namely combining authoritarian leadership styles with democratic and transformational leadership styles.